Molecular cytogenetic characteristics of new spring bread wheat introgressive lines resistant to stem rust - O. A. Baranova; I. G. Adonina; S. N. Sibikeev (Вавиловский журнал генетики и селекции, 2024)
Anticipatory wheat breeding for pathogen resistance is key to preventing economically significant crop losses caused by diseases. Recently, the harmfulness of a dangerous wheat disease, stem rust, caused by Puccinia graminis f. sp. tritici, was increased in the main grain-producing regions of the Russian Federation. At the same time, importation of the Ug99 race (TTKSK) is still a possibility. In this regard, the transfer of effective resistance genes from related species to the bread wheat breeding material followed by the chromosomal localization of the introgressions and a marker analysis to identify known resistance genes is of great importance. In this work, a comprehensive analysis of ten spring bread wheat introgressive lines of the Federal Center of Agricultural Research of the South-East Region (L657, L664, L758, L935, L960, L968, L971, L995/1, L997 and L1110) was carried out. These lines were obtained with the participation of Triticum dicoccum, T. timopheevii, T. kiharae, Aegilops speltoides, Agropyron elongatum and Secale cereale. In this study, the lines were evaluated for resistance to the Ug99 race (TTKSK) in the Njoro, Kenya. Evaluation of introgression lines in the field for resistance to the Ug99 race (TTKSK) showed that four lines were immune, two were resistant, three were moderately resistant, and one had an intermediate type of response to infection. By cytogenetic analysis of these lines using fluorescent (FISH) and genomic (GISH) in situ hybridization, introgressions from Ae. speltoides (line L664), T. timopheevii (lines L758, L971, L995/1, L997 and L1110), Thinopyrum ponticum = Ag. elongatum (2n = 70) (L664, L758, L960, L971, L997 and L1110), as well as introgressions from T. dicoccum (L657 and L664), T. kiharae (L960) and S. cereale (L935 and L968) were detected. Molecular markers recommended for marker-oriented breeding were used to identify known resistance genes (Sr2, Sr25, Sr32, Sr1A.1R, Sr36, Sr38, Sr39 and Sr47). The Sr36 and Sr25 genes were observed in lines L997 and L1110, while line L664 had the Sr39+Sr47+Sr25 gene combination. In lines L935 and L968 with 3R(3D) substitution from S. cereale, gene resistance was presumably identified as SrSatu. Thus, highly resistant to both local populations of P. graminis and the Ug99 race, bread wheat lines are promising donors for the production of new varieties resistant to stem rust.